Joint physical custody of children in Europe: A growing phenomenon - Hakovirta Mia; Meyer Daniel R; Salin Milla; Lindroos Eija; Haapanen Mari (MAX PLANCK INST DEMOGRAPHIC RESEARCH, 2025)
BACKGROUND
Large-scale cross-country comparisons of children's physical custody (which parent the child lives with after separation) are dated and limited in the age range of children considered.
OBJECTIVE
We document the level of sole and joint physical custody (JPC, both equal and unequal) for children in European countries using data from 2021.
METHODS
This article uses a new module on the living arrangements of children from the European Union Statistics on Income and Living Conditions survey. Our final sample comprises 9,102 children from 17 European countries. Analysis is descriptive.
RESULTS
One in eight children in separated families has equal JPC arrangements; another 8.2% spend at least one-third of their time with each parent (but not exactly half-time), so 20.7% have some type of JPC. Direct comparisons with previous estimates show a doubling of the prevalence of JPC in less than 20 years. Substantial cross-national variation exists: In the Northern European countries, Belgium, France, Slovenia, and Spain, children are most likely zo have JPC. Children in the age groups 6-10 and 11-15 are more likely to have JPC than younger or older children.
CONCLUSIONS
Compared to previous studies with data from 2002-2010, there has been an increase in JPC for children from separated families in Europe. Cross-country differences are large, but growth is not limited to a few countries. This paper improves on previous cross -national analyses by using more recent data, incorporating all ages of children, and considering unequal and well as equal time.